A near infrared dye-coated silver nanoparticle/carbon dot nanocomposite for targeted tumor imaging and enhanced photodynamic therapy. Issue 1 (19th December 2019) - Liu, Rongjun; Yang, Zhengmin; Zhang, Liangliang; Zhao, Jingjin; Hou, Cheng; Zhao, Shulin
Abstract : A NIR dye-coated silver nanoparticle/carbon dot nano-composite (CyOH–AgNP/CD) was synthetized as a novel nanophotosensitizer for targeted tumor imaging and high-efficiency PDT. The CyOH–AgNP/CD exhibit potential for future clinical imaging-guided PDT. Abstract : An excellent photosensitizer for imaging-guided high efficiency photodynamic therapy (PDT) requires certain features, such as near-infrared (NIR) light emission, high singlet-to-triplet intersystem crossing (ISC) efficiency, and tumor targeting. However, synthetizing photosensitizers that meet the aforementioned characteristics still remains a challenge. In this study, we synthetized a NIR dye (CyOH)–coated silver nanoparticle/carbon dot nanocomposite (CyOH–AgNP/CD) as a novel nanophotosensitizer for targeted tumor imaging and high-efficiency PDT. The CyOH–AgNP/CD nanophotosensitizer was constructed using a NIR dye (CyOH) and an AgNP/CD nanohybrid via Ag–O interaction. Relative to the AgNP/CD nanohybrid, CyOH–AgNP/CD exhibited a high singlet oxygen yield, mitochondrial accumulation, superior tissue penetration of 660 nm laser irradiation, and enhanced tumor targeting. The developed nanophotosensitizer exerted a higher antitumor effect than the CyOH dye or AgNP/CD nanohybrid. This result provides a new idea for the design of excellent photosensitizers that can benefit high-efficiency PDT.